Teaching Career Development from a Cognitive Developmental Perspective - Young, Richard A. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper, the cognitive developmental paradigm is proposed for developing and teaching career development courses in secondary schools. This model may be useful in redressing the reluctance with which some educators and students view these courses. Two goals are identified based on this model: formal operational reasoning and experience as a reflective thinker. In addition, the major Piagetian constructs of interaction, equilibration, assimilation and accommodation are pro- posed as a means of intervening in both the structure and function of the career thinking of adolescents. Thus, the developmental paradigm provides a single frame- work in which career development courses can be considered both educational and developmental.